2013
DOI: 10.1021/jf305233t
|View full text |Cite
|
Sign up to set email alerts
|

Novel Isoflavone Glucosides in Groundnut (Apios americana Medik) and Their Antiandrogenic Activities

Abstract: Isoflavone glucosides (2'-hydroxy,5-methoxy genistein-7-O-glucoside (1), 2'-hydroxy genistein-7-O-gentibioside (2), 5-methoxy genistein-7-O-glucoside (3), 3',5-dimethoxy genistein-7-O-glucoside (4), 2'-hydroxy genistein-7-O-glucoside (5), genistein-7-O-gentibioside (6), 2'-hydroxy,5-methoxy genistein-4',7-O-diglucoside (7), and 2'-hydroxy genistein-4',7-O-diglucoside (8)) were isolated from the groundnut of Apios americana Medik. Their structures were elucidated on the basis of HR-ESI-MS and 1D- and 2D-NMR ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 14 publications
0
23
0
Order By: Relevance
“…However, poor relationships were observed between estrogenic activity and antioxidant activity, and between α-glucosidase inhibitory activity and antioxidant activity. One hundred grams of Apios tuber contains approximately 60 mg of genistein (mainly as genistein diglucoside 6,7) ) and 20-40 mg of 1-4 (as their glucosides, 7) ) and 100 g of soy bean contains 80 mg of genistein (mainly as genistin). We usually eat Apios tuber after cooking (boiled or fried), and the reduction of isoflavone glucosides in Apios after cooking was not observed on HPLC analyses (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, poor relationships were observed between estrogenic activity and antioxidant activity, and between α-glucosidase inhibitory activity and antioxidant activity. One hundred grams of Apios tuber contains approximately 60 mg of genistein (mainly as genistein diglucoside 6,7) ) and 20-40 mg of 1-4 (as their glucosides, 7) ) and 100 g of soy bean contains 80 mg of genistein (mainly as genistin). We usually eat Apios tuber after cooking (boiled or fried), and the reduction of isoflavone glucosides in Apios after cooking was not observed on HPLC analyses (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, 7) we identified 7 rare and new isoflavone glucosides other than genistein and genistein glucosides in the tuber of Apios and examined their estrogen receptor (ER) binding activities, androgen receptor (AR) binding activities, and androgen antagonistic activities. Our findings revealed that 2'-OH genistein-7-O-gentibioside and 2′-OH genistein-7-Oglucoside possessed moderate anti-androgenic activities.…”
mentioning
confidence: 99%
“…Antiandrogenic chemicals also occur naturally in plants. 76 3, 3′-Diindolylmethane (DIM) is an effective anti-androgen that is present in cruciferous vegetables, such as broccoli, Brussels' sprouts, cabbage and kale. Mahanine inhibits the growth and induces apoptosis in both androgen-responsive, LNCaP and androgen-independent, PC3 cells.…”
Section: Natural Antiandrogensmentioning
confidence: 99%
“…The tubers of A. americana grow to a depth of about 100 cm, and form knots in intervals of about 5 and 10 cm [ 1 , 2 ]. Groundnuts have been used as a traditional health food by the North American Indians [ 2 , 3 ]. The nutrients of these roots were previously reported to include fatty acid, amino acid, and carbohydrate compositions, and a high content of protein (over 12%) [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Groundnuts have been used as a traditional health food by the North American Indians [ 2 , 3 ]. The nutrients of these roots were previously reported to include fatty acid, amino acid, and carbohydrate compositions, and a high content of protein (over 12%) [ 3 , 4 ]. Recently, isoflavonoids, such as genistein, barpisoflavone A, 2′-hydroxygenistein, 5-methylgenistein, 2′-hydroxy genistein-7- O -gentibioside, 2′-hydroxy,5-methoxy genistein-4′,7- O -diglucoside, and 2′-hydroxy genistein-7- O -glucoside, were isolated from the tubers of A. americana [ 3 , 5 ].…”
Section: Introductionmentioning
confidence: 99%